Self-optimisation: Conceptual, discursive and historical perspectives - Daniel Nehring (Current Sociology, 2023)
Self-optimisation has arguably become a central socio-cultural trend in contemporary Western societies. The imperative to optimise our ways of thinking, feeling and interacting with others features prominently in public discourse, and a range of commercial products and services are available to assist us in our quest to become the best version of our selves. However, self-optimisation has so far received scant attention in sociological research. Addressing this knowledge gap, we aim to introduce self-optimisation as a concept for sociological analysis. We first situate self-optimisation in several closely linked strands of academic debate, on transformations of self-identity under conditions of globalisation and neo-liberal capitalism, and on the spread of a therapeutic culture. We then map the socio-cultural antecedents of self-optimisation, survey its rise as a salient public discourse and as a form of everyday practice and consider some political implications. In the conclusion, we set out an agenda for further research on self-optimisation and discuss its conceptual and empirical relevance beyond the Global Northwest.